2020
DOI: 10.1186/s13287-020-01662-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic preconditioning of human urine-derived stem cell-laden small intestinal submucosa enhances wound healing potential

Abstract: Background Urine-derived stem cells (USCs) are a valuable stem cell source for tissue engineering because they can be harvested non-invasively. Small intestine submucosa (SIS) has been used as scaffolds for soft tissue repair in the clinic. However, the feasibility and efficacy of a combination of USCs and SIS for skin wound healing has not been reported. In this study, we created a tissue-engineered skin graft, termed the SIS+USC composite, and hypothesized that hypoxic preconditioning would i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 66 publications
1
27
0
Order By: Relevance
“…Massive signaling occurs which needs to be regulated and may take longer until tissue regeneration occurs compared to other cell dosages. It has been shown that MSCs reduce hypoxia-induced apoptosis [57] and additionally showed a beneficial initial inflammatory upregulation in MSCs that prevents hypertrophic scar formation [54,[58][59][60], which would be in line with our findings. For very low initial cell concentrations, the cell numbers may be declining since the critical threshold of hemostasis is not reached, but the paracrine signals may provide the neighboring cells in the wound bed a very early proliferative healing boost as shown in the results.…”
Section: Discussionsupporting
confidence: 92%
“…Massive signaling occurs which needs to be regulated and may take longer until tissue regeneration occurs compared to other cell dosages. It has been shown that MSCs reduce hypoxia-induced apoptosis [57] and additionally showed a beneficial initial inflammatory upregulation in MSCs that prevents hypertrophic scar formation [54,[58][59][60], which would be in line with our findings. For very low initial cell concentrations, the cell numbers may be declining since the critical threshold of hemostasis is not reached, but the paracrine signals may provide the neighboring cells in the wound bed a very early proliferative healing boost as shown in the results.…”
Section: Discussionsupporting
confidence: 92%
“…GAPDH (rabbit, 1:1,000, GeneTex, Irvine, CA, USA) was used as an internal control and the secondary antibody was goat anti-rabbit antibody (1:2,500, ZSBIO, Beijing, China). To detect chondrogenesis-related gene expression, qRT-PCR was performed as previously described [ 24 ]. Chondrogenesis-related genes included Agg , Sox9 , and Col II .…”
Section: Methodsmentioning
confidence: 99%
“…USCs can be expanded both in normoxia (21% O 2 ) or hypoxia with hypoxia being shown to induce higher proliferation rate but also to increase the USC potential for angiogenesis in a wound healing model[ 25 , 26 ].…”
Section: Isolation and Characterization Of Urine Stem Cellsmentioning
confidence: 99%